Enhancing Employee Performance: The Role of Talent Management and Employee Engagement at PT. Jamu Borobudur - Joko Kurniyanto (Journal of Economic Perspectives and Business Innovation, 2024)
Abstract This study aims to examine the role of talent management and employee engagement in enhancing employee performance at PT. Jamu Borobudur. In a highly competitive business environment, effective human resource management is essential to maintain organizational performance and sustainability. This research employs a quantitative approach using survey data collected from employees of PT. Jamu Borobudur. The findings indicate that talent management practices, including talent identification, development, and retention, have a significant positive effect on employee performance. Furthermore, employee engagement is found to strengthen employees’ commitment, motivation, and involvement in achieving organizational goals. The results also show that employee engagement mediates the relationship between talent management and employee performance. The study concludes that the integration of effective talent management strategies and high levels of employee engagement is crucial to improving employee performance and supporting long-term organizational success. Keywords talent management, employee engagement, employee performance, human resource management, organizational performance